How does information disclosure affect liquidity? Evidence from an Emerging Market (2018)
Cross-sectional models positively relate firm information disclosure with stock liquidity, but dynamic models in news releases days show an opposite relation. We address this puzzle by studying the effects of information arrival on liquidity and its determinants. We use trade and quote data from Colombia for 2015 and 2016, along with the complete database of news releases as reported by companies to the regulator. The results of Panel data and PVAR models suggest that news releases increase both informed and uninformed trading. All in all, the temporal negative effect of news releases on liquidity is explained by increasing asymmetric information.